A design of codec based on HDMI2.0 - Wei Guo (Dianzi Jishu Yingyong, 2018)
Based on the analysis of High-Definition Multimedia Interface(HDMI)2.0 specification, the circuit of codec was designed with the hardware description language, and the prototype verification was implemented on the FPGA platform. The circuit of codec not only occupied less logical resource, but also compatible with HDMI1.4 and HDMI2.0 specification. The verification results show that the design can realized the functions of codec and meet the requirements of HDMI2.0 interface. It could be applied to system design.